2011
DOI: 10.1002/mar.20386
|View full text |Cite
|
Sign up to set email alerts
|

White response to potentially discriminatory actions in a services setting

Abstract: Discrimination in the marketplace is a significant problem for many blacks and for service providers. However, recent research suggests that some whites may respond similarly to blacks when they witness what they perceive to be a discriminatory act in a service encounter. Using an experimental design methodology, this research investigates the extent to which this occurs. The degree to which an observing customer values the other customer's welfare and feels empathy has been found to explain differences in ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 34 publications
3
16
2
Order By: Relevance
“…Our findings are analogous to those of Baker and Meyer (2011) who showed that differences in Whites' level of empathy influenced their perception of the severity of a service failure in a restaurant, the degree of anger they reported feeling, and their attribution of the incident to racial discrimination. Baker and Meyer (2011) posited that when and why Whites have empathetic reactions to a service failure in a store may be a function of the value they place on the welfare of the other person.…”
Section: Effects Of Psdsupporting
confidence: 90%
See 3 more Smart Citations
“…Our findings are analogous to those of Baker and Meyer (2011) who showed that differences in Whites' level of empathy influenced their perception of the severity of a service failure in a restaurant, the degree of anger they reported feeling, and their attribution of the incident to racial discrimination. Baker and Meyer (2011) posited that when and why Whites have empathetic reactions to a service failure in a store may be a function of the value they place on the welfare of the other person.…”
Section: Effects Of Psdsupporting
confidence: 90%
“…Most participants found the salesperson's behavior to be highly unacceptable and were angry about the situation. Furthermore, the presence of the White shopper who received good service provided a context in which racial discrimination could be more easily inferred (see similar findings by Baker & Meyer, 2011;Baker et al, 2008). While these limitations led to small effect sizes, we still detected differences based on participants' own race/ethnicity and PSD.…”
Section: Limitationscontrasting
confidence: 38%
See 2 more Smart Citations
“…With return to a reflection on race in public discourse that accompanied the election of Barak Obama as President and the contention that we may now live in a post‐racial America (Valentino and Brader ), it appears an apt time to revisit this issue. The marketplace has a storied history of consumer racial discrimination, and reconsideration allows for a contemporary examination of issues regarding shopping while “nonwhite” (Baker and Meyer ; Bennett, Hill, and Oleksiuk ). To this end, we ask the following questions to guide discovery: How widespread are experiences of racial discrimination among consumer groupings, how does it manifest, and how is it perceived across minority and majority consumers?…”
mentioning
confidence: 99%